Conversion to Islam in the Balkans: Kisve bahası petitions and Ottoman social life, 1670-1730 - Minkov, Anton (The Ottoman Empire and its heritage, 2004)
This volume offers a new approach to the subject of conversion to Islam in the Balkans. It reconstructs the stages of the Islamization process from the fifteenth to the nineteenth centuries and examines the factors and stimuli behind it. The practice of accepting Islam in the front of the sultan, characteristic of the last period of Islamization, and granting to new Muslims an amount of money known as kisve bahasi, is shown in the context of Ottoman social development. An innovative structural analysis of the petitions requesting kisve bahasi leads to examining the origins of the practice and